Confounding Images : Photography and Portraiture in Antebellum American Fiction - Williams, Susan S. (University of Pennsylvania Press, 2016)
Susan Williams recovers the literary and cultural significance of early photography in an important rereading of American fiction in the decades preceding the Civil War. The rise of photography occurred simultaneously with the rapid expansion of magazine publication in America, and Williams analyzes the particular role that periodicals such as Godey's Lady's Book, Burton's Gentleman's Magazine, and Atkinson's Casket played in defining how photography was received. At the center of the book are readings of a stunning array of fiction by forgotten and canonical writers alike, including Edgar Allan Poe, Louisa May Alcott, and Sarah Hale, as well as extended interpretations of Nathaniel Hawthorne's House of the Seven Gables and The Marble Faun and Herman Melville's Pierre. In a concluding section, Williams offers a view of the fictional portrait in the later nineteenth century, when the proliferation of illustrated books once again transformed the relation between word and image in American culture.